New antituberculotics originated from salicylanilides with promising in vitro activity against atypical mycobacterial strains - Imramovský, Ales; Vinsová, Jarmila; Férriz, Juana Monreal; Dolezal, Rafael; Jampílek, Josef; Kaustová, Jarmila; Kunc, Filip (Bioorganic & medicinal chemistry, 2009)
A new series of 30 N-protected amino acid esters were prepared as a part of ongoing search for new anti-tuberculosis active salicylanilides. The esters possess high in vitro activity against Mycobacterium tuberculosis, Mycobacterium avium, and two strains of Mycobacterium kansasii, where one is an isolate from the patient, with MIC in the range 1-32 micromol/L for all tested strains. The prepared esters can be considered as prodrugs with better bio-availability and as more efficient transport forms through the mycobacterial cell membranes due to the higher lipophilicity. The experimental and calculated lipophilicity, stability, antituberculotic activity, cytotoxicity as well as the quantitative structure-activity relationships (QSARs) explored by the Intelligent Problem Solver (IPS) in Trajan Neural Network Simulator 6.0 are presented.
Keywords: Quantitative Structure-Activity Relationship; kvantitativní vztahy mezi strukturou a aktivitou; salicylanilidy; netuberkulózní mykobakterie; Salicylanilides; Antitubercular Agents; antituberkulotika; Nontuberculous Mycobacteria; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions; esterifikace; Esterification